2017
DOI: 10.1371/journal.pone.0178039
|View full text |Cite
|
Sign up to set email alerts
|

Soil texture analysis revisited: Removal of organic matter matters more than ever

Abstract: Exact estimates of soil clay (<2 μm) and silt (2–20 μm) contents are crucial as these size fractions impact key soil functions, and as pedotransfer concepts based on clay and silt contents are becoming increasingly abundant. We examined the effect of removing soil organic matter (SOM) by H2O2 before soil dispersion and determination of clay and silt. Soil samples with gradients in SOM were retrieved from three long-term field experiments each with uniform soil mineralogy and texture. For soils with less than 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
31
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 26 publications
10
31
0
1
Order By: Relevance
“…Since all the Bouyoucos treatments evaluated in this study estimated the silt concentration as the difference between 100 percent and the percent sand and clay (Equation 3), any analytical errors would impact the estimation of the silt content when determining these two fractions. This nding is consistent with the observations of [22] who reported that the silt fraction was systematically overestimated when soil organic matter was not removed. The average silt content determined using the Bouyoucos methods was 6.89% (P = <0.001) lesser than that determined using the Pipette method.…”
Section: Comparison Of the Pipette Methods With Bouyoucos Treatmentssupporting
confidence: 93%
See 3 more Smart Citations
“…Since all the Bouyoucos treatments evaluated in this study estimated the silt concentration as the difference between 100 percent and the percent sand and clay (Equation 3), any analytical errors would impact the estimation of the silt content when determining these two fractions. This nding is consistent with the observations of [22] who reported that the silt fraction was systematically overestimated when soil organic matter was not removed. The average silt content determined using the Bouyoucos methods was 6.89% (P = <0.001) lesser than that determined using the Pipette method.…”
Section: Comparison Of the Pipette Methods With Bouyoucos Treatmentssupporting
confidence: 93%
“…This necessitates the pre-treatment of the soil samples to remove organic matter before texture analysis. This observation is consistent with the ndings of [22], who reported underestimation of the clay content in samples where organic matter was not removed. The 4%Calgon treatment was negatively correlated with the Pipette method (r = -0.712; P-value = 0.021) at the 0.05 level which can be attributed to the low concentration of the dispersant that could have led to incomplete dispersion.…”
Section: Comparison Of the Pipette Methods With Bouyoucos Treatmentssupporting
confidence: 92%
See 2 more Smart Citations
“…Soil texture and SOC data for the Highfield experiment at Rothamsted Research, UK (51°80′N, 00°36′W), were extracted from Jensen et al . (). This experiment is on a silt loam soil belonging to the Batcombe series; the parent material includes a silty (loess‐containing) deposit overlying and mixed with clay‐with‐flints (Avery & Catt, ).…”
Section: Methodsmentioning
confidence: 97%